A Highly Stable Two‐Dimensional Copper(II) Organic Framework for Proton Conduction and Ammonia Impedance Sensing. Issue 42 (25th June 2018) - Sun, Zhibing; Yu, Shihang; Zhao, Lili; Wang, Jifeng; Li, Zifeng; Li, Gang
Abstract: This work reports the design and fabrication of a proton conductive 2D metal–organic framework (MOF), [Cu( p ‐IPhHIDC)] n (1 ) ( p ‐IPhH3 IDC=2‐( p ‐ N ‐imidazol‐1‐yl)‐phenyl‐1  H ‐imidazole‐4, 5‐dicarboxylic acid) as an advanced ammonia impedance sensor at room temperature and 68–98 % relative humidity (RH). MOF1 shows the optimized proton conductivity value of 1.51×10 −3  S cm −1 at 100 °C and 98 % RH. Its temperature‐dependent and humidity‐dependent proton conduction properties have been explored. The large amount of uncoordinated carboxylate groups between the layers plays a vital role in the resultant conductivity. Distinctly, the fabricated MOF‐based sensor displays the required stability toward NH3, enhanced sensitivity, and notable selectivity for NH3 gas. At room temperature and 68 % RH, it gives a remarkable gas response of 8620 % to 130 ppm NH3 gas and lower detection limit of 2 ppm towards NH3 gas. It is also found that the gas response of the ammonia sensor increases linearly with the increase of NH3 gas concentration under 68–98 % RH and room temperature. Moreover, the sensor indicates excellent reversibility and selectivity toward NH3 versus N2, H2, O2, CO, CO2, benzene, and MeOH. Based on structural analyses, activation energy calculations, water and NH3 vapor absorptions, and PXRD determinations, proton conduction and NH3 sensing mechanisms are suggested. Abstract : Ammonia detection : Proton conductivity and ammonia sensing properties of a 2D Cu‐based metal–organic framework (MOF) were explored. The experimental results reveal that the proton conductivity of MOF1 reaches a maximum of 1.51×10 −3  S cm −1 at 100 °C and 98 % relative humidity (RH). At room temperature and 68 % RH, the MOF‐based sensor indicates a remarkable gas response of 8620 % to 130 ppm NH3 gas and lower detection limit of 2 ppm towards NH3 gas.